Impact of green innovation on the sustainable performance of food industrial firms applying green industry initiatives under the Green Industry Project of the Ministry of Industry of Thailand - Monika Tantayanubutr; Vinai Panjakajornsak (My University, 2017)
This research examines the impact of green innovation on the sustainable performance of Thai food industry implementing green industry initiatives in compliance with the national Green Industry Project.The correlation analysis was conducted on green supply chain integration (GSCI) and corporate social responsibility (CSR) as key influencing variables, while the green innovation was a moderator.A total of 441 samples were received from the total population of 8,520 accredited Green Industry Mark enterprises (GIM) (2016).Structural equation modeling (SEM) was employed to test the empirical data derived from surveys, which were collected from entrepreneurs and chief executive officers involved in the Thai food industry.The model indicated the absolute fit indices, confirming the validity and reliability of the SEM analysis.The findings confirmed the positive relationship of the selected key factors and their effect on the sustainable performance.
Keywords: Christian ministry; Green innovation; Green food; Environmental Sustainability in Business